A necroptosis -related signature for predicting prognosis and immunotherapy in hepatocellular carcinoma - Fu, Xing; Yang, Yuling; Zhang, Xiaozhi (Frontiers in Genetics, 2022)
Background: Hepatocellular Carcinoma (HCC) is an aggressive tumor with an inferior prognosis. Necroptosis is a new form of programmed death that plays a dual effect in cancer development. However, the role of necroptosis-related genes（NRGs）in HCC remains unknown. Methods: All datasets of HCC were downloaded from publicly available databases. The consensus clustering analysis classifies patients with HCC into different subtypes. The univariate cox analysis and Least Absolute Shrinkage and Selection Operator (LASSO) cox regression were used to develop a necroptosis-related signature. Kaplan-Meier curves, Receiver operating characteristics (ROC), and Cox regression analyses were applied to evaluate prognostic performance of signature. Tumor Immune Dysfunction and Exclusion (TIDE) and tumor mutation burden (TMB) analysis predicted immune response. Results: A total of 36 differentially expressed NRGs (DE-NRGs) were screened between HCC and normal tissue. Based on the DE-NRGs, HCC patients were classified into three subtypes, with significant immune infiltration and survival differences. The prognostic signature was established based on eight NRGs. Survival rates were significantly different between the low- and high-risk group. The risk score was an independent prognostic factor. The high-risk group had higher TMB and the expression of immune checkpoints and lower TIDE score, indicating the high risk-score patients may be more suitable for immunotherapy. We also find a higher risk score in the immunotherapy response group (PR/CR) than the non-response group (PD/SD) by datasets of IMvigor210. Conclusion: We developed a new necroptosis-related signature for predicting prognosis and correlated with immunotherapy.